Ancient sites as ethnomathematics for strengthening Profil Pelajar Pancasila in Malang - Wikan Budi Utami; Sri Hariyani; Fikri Aulia (Inovasi Kurikulum, 2024)
This study aims to determine the effectiveness of learning mathematics using ancient sites as a source of learning and to raise students' awareness of protecting and preserving ancient sites. The research design used was the pre and post-test group design with two groups. The experimental and control groups will be given a pretest before treatment and a posttest after treatment. The population used was 148 grade IV elementary school students, and the sample used was 120 people consisting of 60 experimental class students and 60 control class students. Data analysis in this study used statistical data processing software IBM SPSS version 27. Based on the summary of the independent t-test results, the value of Sig. (2-tailed) on the post-test data is 0.001. This value is smaller than the specified significance level of 0.05. This means that the averages of the experimental and control groups at the post-test were significantly different. The results showed that the archaeological site of Singosari temple can be used as a source of learning mathematics for elementary schools and can increase students' understanding of the preservation of ancient sites as a form of strengthening the Profil Pelajar Pancasila. AbstrakPenelitian ini mengungkap keefektifan pembelajaran matematika dengan menggunakan situs purbakala sebagai sumber belajar serta meningkatkan kesadaran siswa untuk menjaga dan melestarikan situs purbakala. Desain penelitian yang digunakan adalah pre and posttest group design dengan dua kelompok. Kelompok eksperimen dan kontrol akan diberikan pretest sebelum perlakuan dan posttest setelah perlakuan design dengan dua kelompok. Kelompok eksperimen dan kontrol akan diberikan pretest sebelum perlakuan dan posttest setelah perlakuan. Populasi yang digunakan sebanyak 148 siswa sekolah dasar kelas IV dan sampel yang digunakan sebanyak 120 orang yang terdiri dari 60 siswa kelas eksperimen dan 60 siswa kelas kontrol. Analisis data pada penelitian ini menggunakan software pengolah data statistik IBM SPSS versi 27. Berdasarkan rangkuman hasil uji t independen diperoleh nilai Sig. (2-tailed) pada data posttest 0,001. Nilai ini lebih kecil dari tingkat signifikansi yang ditentukan yaitu 0,05. Artinya rata-rata kelompok eksperimen dan kontrol pada saat posttest berbeda secara signifikan. Hasil penelitian menunjukkan bahwa situs arkeologi Candi Singosari dapat dijadikan sebagai sumber pembelajaran matematika untuk sekolah dasar dan dapat meningkatkan pemahaman siswa terhadap pelestarian situs purbakala sebagai bentuk penguatan profil siswa Pancasila.Kata Kunci: Ethnomathematic; Profil Pelajar Pancasila; situs purbakala; sumber belajar